2016
DOI: 10.4322/acr.2016.045
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in infective endocarditis

Abstract: The case fatality rate of infective endocarditis (IE) is high and is associated with varying causes. Among them, acute myocardial infarction due to an embolism in a coronary artery is rare; the incidence of this complication in the setting of IE is reported to be up to 1.5%. We report a case of sudden death in a 22-year-old woman diagnosed with systemic lupus erythematosus who was referred to the Cardiology Center for the treatment of mitral valve incompetence due to IE. She was hemodynamically stable with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Infective endocarditis is associated with a broad array of a complications; cardiac, neurologic, renal, musculoskeletal, and systemic complications related to the infection (embolization, metastatic infection, and aneurysm) [5,6]. Some autopsy case reports regarding causes of death, which are due to fatal complications, have previously been published [7,10,11,14]. In this case, although the patient did not have fatal complications which have been reported in past such cases, he subsequently died as a result of this uncontrollable infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infective endocarditis is associated with a broad array of a complications; cardiac, neurologic, renal, musculoskeletal, and systemic complications related to the infection (embolization, metastatic infection, and aneurysm) [5,6]. Some autopsy case reports regarding causes of death, which are due to fatal complications, have previously been published [7,10,11,14]. In this case, although the patient did not have fatal complications which have been reported in past such cases, he subsequently died as a result of this uncontrollable infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some autopsy case reports regarding causes of death have previously been published. These cases reported that the condition of patients with infective endocarditis worsened drastically, and they suddenly died from fatal complications, such as acute severe heart failure, cerebrovascular major embolism, and hemorrhage or acute coronary embolism [6][7][8][9][10][11][12][13]. In these cases, early diagnosis did not necessarily have an important role because of the unpredictable and relatively rare situation.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, the classic findings of vegetation in infective endocarditis are tissue infiltration of neutrophils and fibrin deposition along with the implicated bacteria can be identified using gram stain. In rare cases, a vegetative embolus may lodge in a coronary artery which can be the cause of SCD, in these circumstances the embolus has the same characteristic microscopic picture of the original vegetation [5]. The hearts of patients who suffered from arrhythmogenic right ventricular dysplasia exhibit microscopic features of fat infiltrating the myocardium, fibrofatty replacement along with patchy areas of myocarditis [18].…”
Section: Microscopic Investigationsmentioning
confidence: 99%
“…Infective endocarditis is another infectious cardiac disease which can induce SCD due to many causes. On gross examination of the heart, one can detect the presence of a vegetation on the infected valve, erosion of the underlying tissue, the chordae tendineae may be disrupted resulting in their rupture [5]. Congenital heart diseases occupy a high rank in the causes of SCD in children, with coarctation of the aorta (CoA) and transposition of the great vessels in the forefront [22].…”
Section: Macroscopic Studiesmentioning
confidence: 99%
See 1 more Smart Citation